Revision of Emmenomma Simon (Amaurobiidae, Macrobuninae) - Almeida-Silva, Lina M.; Griswold, Charles E.; Brescovit, Antonio D. (Zootaxa, 2015)
The genus Emmenomma is revised and now includes three species from Southern Chile, Argentina and Falkland Islands (Islas Malvinas). The type species Emmenomma oculatum is redescribed and considered a senior synonym of E. beauchenicum. Emmenomma oculatum obscurum is removed from synonymy with E. oculatum, raised to the species level and redescribed; the male of this species remains unknown. A new species, Emmenomma joshuabelli sp. nov. is described. The presence of a grate shaped tapetum outside the Lycosoidea clade is described. Detailed images are provided for all known species.